All-silicone elastic composites with counter-intuitive piezoelectric response, designed for electromechanical applications. Issue 28 (5th July 2017) - Racles, Carmen; Dascalu, Mihaela; Bele, Adrian; Tiron, Vasile; Asandulesa, Mihai; Tugui, Codrin; Vasiliu, Ana-Lavinia; Cazacu, Maria
Abstract : PDMS-based stretchable elastomeric composites with cross-linked polar silicone particles as fillers exhibit piezoresponse, improved dielectric properties and tunable mechanical behaviour. Abstract : New all-silicone composite materials were prepared using polar silicone particles dispersed within a high molecular weight polydimethylsiloxane (PDMS) matrix. Polar silicones with either CN or Cl groups attached to the polysiloxane chain in similar proportions were prepared by appropriate post-polymerization reactions and submicron particles were obtained and stabilized with a hydrophobic commercial surfactant, Pluronic L81, while the polar polymers were cross-linked within the particles in most cases. The mechanical and dielectric properties of the all-silicone composites were measured and discussed as a function of the nature and number of polar groups in the filler particles and in correlation with morphological aspects. Soft elastomeric materials with a Young's modulus of 0.12–0.5 MPa, dielectric permittivity up to 4.7 at 10 4 Hz and dielectric strength up to 63 V μm −1 were obtained, and promising electromechanical performance resulted from theoretical calculations. Dielectric relaxation spectrometry at varying temperatures revealed dynamic relaxations in agreement with DSC data, and high dielectric relaxation strength values (Δ ε ) were calculated. We also report for the first time piezoelectric behaviour of all-polymer composites containing amorphous components, measured using Piezoelectric Force Microscopy (PFM) at ambient temperature (above T g ) without poling. Average longitudinal piezoelectric coefficients ( d 33 ) of 24 and 13 pm V −1 were found for composites with cyano- and chloro-silicones, respectively. The variation of d 33 with stretching was also followed and explained in correlation with morphological aspects. The promising properties of the all-silicone composites create the premises for possible applications as stretchable electronics, including tactile sensors, acoustic transducers and wearable devices.